Design and construction of light-regulated gene transcription and protein translation systems in yeast P. Pastoris - Siyu Zhang; Jiazhen Zhang; Ru Lin; Chaoyu Lu; Bohao Fang; Jiacheng Shi; Tianyi Jiang; Mian Zhou (Journal of Advanced Research)
Introduction: P. pastoris is a common host for effective biosynthesis of heterologous proteins as well as small molecules. Accurate regulation of gene transcription and protein synthesis is necessary to coordinate synthetic gene circuits and optimize cellular energy distribution. Traditional methanol or other inducible promoters, natural or engineered, have defects in either fermentation safety or expression capacity. The utilization of chemical inducers typically adds complexity to the product purification process, but there is no other well-controlled protein synthesis system than promoters yet. Objective: The study aimed to address the aforementioned challenges by constructing light-regulated gene transcription and protein translation systems with excellent expression capacity and light sensitivity. Methods: Trans-acting factors were designed by linking the N. crassa blue-light sensor WC-1 with the activation domain of endogenous transcription factors. Light inducible or repressive promoters were then constructed through chimeric design of cis-elements (light-responsive elements, LREs) and endogenous promoters. Various configurations of trans-acting factor/LRE pairs, along with different LRE positions and copy numbers were tested for optimal promoter performance. In addition to transcription, a light-repressive translation system was constructed through the “rare codon brake” design. Rare codons were deliberately utilized to serve as brakes during protein synthesis, which were switched on and off through the light-regulated changes in the expression of the corresponding pLRE-tRNA. Results: As demonstrated with GFP, the light-inducible promoter 4pLRE-cPAOX1 was 70 % stronger than the constitutive promoter PGAP, with L/D ratio = 77. The light-repressive promoter PGAP-pLRE was strictly suppressed by light, with expression capacity comparable with PGAP in darkness. As for the light-repressive translation system, the “triple brake” design successfully eliminated leakage and achieved light repression on protein synthesis without any impact on mRNA expression. Conclusion: The newly designed light-regulated transcription and translation systems offer innovative tools that optimize the application of P. pastoris in biotechnology and synthetic biology.